229k views
0 votes
Simplify nine square root of two minus three square root of seven-plus square root of eight minus the square root of twenty-eight.

User Wick
by
4.6k points

2 Answers

4 votes

Answer:

11
√(2) - 5√7

Explanation:

= 9
√(2) - 3
√(7) + 2√2 - 2
√(7)

= 11
√(2) - 3
√(7) - 2
√(7) add similar elements

= 11
√(2) - 5
√(7)

User Tirthraj Barot
by
5.2k points
4 votes

Answer:

= 11√2 - 5√7

Explanation:

9√2 - 3√7 + √8 - √28

= 9√2 - 3√7 + 2√2 - 2√7

add similar elements

= 11√2 - 3√7 - 2√7

= 11√2 - 5√7

User Marleen
by
5.8k points